Children of Men - Cuaron, Alfonso; Juan, Gabriel Yacuzzi; Michelle Hussain; Rob Curling; Jon Chevalier; Rita Davies (Universal Studios, 2007)
n 2027, as humankind faces the likelihood of its own extinction, a disillusioned government agent agrees to help transport and protect a miraculously pregnant woman to a sanctuary at sea where her child's birth may help scientists to save the future of mankind.
Languages: English, Turkish Subtitles: Turkish
Keywords: Drama; Action -- Adventure; Mystery -- SciFi